2016
DOI: 10.1016/j.canlet.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the relative potential of silver, Zinc-oxide and titanium-dioxide nanoparticles against UVB-induced DNA damage for the prevention of skin carcinogenesis

Abstract: Sunscreen formulations containing UVB filters, such as Zinc-oxide (ZnO) and titanium-dioxide (TiO2) nanoparticles (NPs) have been developed to limit the exposure of human skin to UV-radiations. Unfortunately, these UVB protective agents have failed in controlling the skin cancer incidence. We recently demonstrated that silver nanoparticles (Ag-NPs) could serve as novel protective agents against UVB-radiations. Here our goal was to perform comparative analysis of direct and indirect UVB-protection efficacy of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 43 publications
(59 reference statements)
1
39
1
3
Order By: Relevance
“…Previous studies have demonstrated that UV or other carcinogens decreased expression or activity of DNA repair enzymes: tobacco smoke reduced DNA repair enzymes, XPC and OGG1, in lung tissue [32,33]; infrared radiation reduced GADD45a in cultured human fibroblasts [34]. In other studies, UV increased expression of DNA repair enzymes GADD45a [35], XPA, XPC, and RPA1 [36]. Thus, the effects on DNA repair is dependent on the UV dose and time point.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated that UV or other carcinogens decreased expression or activity of DNA repair enzymes: tobacco smoke reduced DNA repair enzymes, XPC and OGG1, in lung tissue [32,33]; infrared radiation reduced GADD45a in cultured human fibroblasts [34]. In other studies, UV increased expression of DNA repair enzymes GADD45a [35], XPA, XPC, and RPA1 [36]. Thus, the effects on DNA repair is dependent on the UV dose and time point.…”
Section: Discussionmentioning
confidence: 94%
“…Sod2 overexpression following AgNPs exposure was reported in different in vivo studies like in C. elegans (Roh et al ) and in the Cape River crab Potamonautes perlatus (Walters et al ). In addition, different in vitro studies like in human immortalized keratinocytes (HaCaT) cells have shown the ability of AgNPs exposure to enhancing Sod2/Cat/Gpx activity (Tyagi et al ). Cat expression showed relevant changes only after silver nitrate exposure, with different patterns according exposure: over‐expression at low dose and downregulation at the highest tested dose.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of TiO 2 NP exposure are still unclear, yet many TiO 2 NP-induced toxic effects have been reported. TiO 2 NPs can cause several adverse effects on mammalian cells, including ROS production [62,63], DNA damage responses [64], proliferation, and the induction of apoptosis [65,66]. Hiroike et al suggested that acicular, but not globular TiO 2 NPs stimulate keratinocytes to produce pro-inflammatory cytokines such as IL-1Îą, IL-1β, IL-6, TNF-Îą, and IL-8 [67].…”
Section: Possible Role Of Inflammasome and Autophagy In Nanoparticmentioning
confidence: 99%